230k views
0 votes
Y=−5x2+ 6x− 3 y=−4x− 3

using elimination or subsutution

User Waxhaw
by
5.5k points

2 Answers

4 votes

I think the answer is:2x-4y=13

START BY USING BODMAS

  1. Brackets
  2. of
  3. division
  4. multiplication
  5. addition
  6. subtraction

y=-(10)+6x-3y=-4x-3

{3+10=13}

{3y+y=4y}

{6x-4x=2x}

4y=+2x-13

=2x-4y=13

I'M NOT SURE OF THE ANSWER THOUGH

User U Rogel
by
6.4k points
8 votes

Explanation:

My math is terrible but I think u should eliminate and substitute.

User Felix Jassler
by
6.0k points